PENJATUHAN PIDANA DI BAWAH ANCAMAN PIDANA MINIMUM DARI KETENTUAN UNDANG-UNDANG NO. 35 TAHUN 2009 TENTANG NARKOTIKA - Sadriyah Mansur (Madani Legal Review, 2017)
This research aimed to investigate the considerations of the judges in stating the sentence which was under the minimum criminal threat as stated in the Ordinance No. 35 of 2009 concerning narcotics: and to investigate the impacts of the criminal punishment of the judges which was under the minimum criminal punishment concerning the legal principles. The research was a normative and empirical research, and the technique of analyzing the data both the primary and secondary data was a qualitative technique. The results of the analysis were presented descriptively in order to illustrate the bases of the judges’ consideration in deciding in the Criminal punishment which was less than the minimum criminal punishment in the their sentence no. 17/Pid.B/2014/PN.Pinrang, less than minimum punishment and the legal principles. The research result indicates that bases of he consideration of the judges in stating the punishment less than the minimum sanction in the sentence No. 17/Pid.B/2014/PN.pinrang were the freedom principles of the judges in doing the legal softening and the legal construction by considering the justice sense: meaning when the legal construction by considering the justice sense: meaning when the legal certainly was in opposite to the justice, the justice should be given a priority, since the judges were not the trumpets of the laws (bouche de la loi or spreekbuis van de wet).